2002
DOI: 10.1074/jbc.m109525200
|View full text |Cite
|
Sign up to set email alerts
|

The Major Extracellular Protease of the Nosocomial Pathogen Stenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia is increasingly emerging as a multiresistant pathogen in the hospital environment. In immunosuppressed patients, these bacteria may cause severe infections associated with tissue lesions such as pulmonary hemorrhage. This suggests proteolysis as a possible pathogenic mechanism in these infections. This study describes a protease with broad specificity secreted by S. maltophilia. The gene, termed StmPr1, codes for a 63-kDa precursor that is processed to the mature protein of 47 kDa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 30 publications
(26 reference statements)
7
87
0
2
Order By: Relevance
“…In vitro data demonstrated that S. maltophilia produces proteases, which can break down the protein components of collagen, fibronectin and fibrinogen, 31,32 and this may contribute to local tissue damage and hemorrhage. 1 Because our present histopathological findings at autopsy demonstrated alveolar hemorrhage and the massive infiltration of Gram-negative rods in lungs without invasion by neutrophils or lymphocytes, S. maltophilia itself might damage lung tissue, which leads to pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data demonstrated that S. maltophilia produces proteases, which can break down the protein components of collagen, fibronectin and fibrinogen, 31,32 and this may contribute to local tissue damage and hemorrhage. 1 Because our present histopathological findings at autopsy demonstrated alveolar hemorrhage and the massive infiltration of Gram-negative rods in lungs without invasion by neutrophils or lymphocytes, S. maltophilia itself might damage lung tissue, which leads to pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotides PrL (5'-CGAGAACGACAACGAGTGCTACA-3') and PrR (5'-CACGGCGGTCTTGTTGGTCA-3') were used to amplify a 0.9 kb internal fragment of the StmPrl gene (GenBank accession no. AJ291488) (13). Both DNA probes were labeled with a-p 32 dATP by the random priming method (Amersham Kit), and Southern hybridization was performed according to Sambrook and Russel (14).…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…It is important to note that in the case of C. muricatus, a molecule with inhibitory activity against subtilisin in the submicromolar level, CmPI-2, has been already isolated [25]. Subtilisins are present in many pathogenic microorganisms required within invasion/proliferation processes [7] [8]. Marine invertebrates live alongside many bacteria and parasites in aquatic environments and they protect themselves against pathogenic infection through their innate immune system, which utilizes several biomolecules for their defense including protease inhibitors [22].…”
Section: Discussionmentioning
confidence: 99%
“…the serine proteases human neutrophil elastase (HNE), subtilisins, dipeptidylpeptidase-IV (DPPIV) and papain-like proteases, such as cathepsin K. The former, which is involved in pulmonary emphysema, rheumatoid arthritis and cystic fibrosis, is released from human polymorphonuclear leukocytes in response to inflammatory stimuli and it is responsible for the degradation of connective tissue proteins [5] [6]. Subtilisins are involved in invasion processes of many pathogenic parasites and bacteria, such as Plasmodium falciparum and the nosocomial pathogen Stenotrophomonas maltophilia, [7] [8]. Dipeptidylpeptidase-IV is implicated in human systemic conditions, such as diabetes mellitus, cancer and inflammatory diseases [9] [10].…”
Section: Introductionmentioning
confidence: 99%